Measuring performance of universities in fragile countries - Mohamed, Shafie Sharif; Islam, Rafikul; Zainudin, Dolhadi (IIUM Press, International Islamic University Malaysia, 2017)
Measuring performance of a university is important as it gives the idea of the position of the university and also activities can be initiated to further improve its performance. However, existing performance measurement models such as Malcolm Baldridge National Quality Award are developed for the universities in developed and developed countries. There is none to measure performance of the universities in war-torn fragile countries. This present book presents an elegant method that can be applied to measure performance of the universities in various fragile countries.